Association of Whole Grain Consumption and Cognitive Function in Biracial Population Sample. (14th June 2022) - Liu, Xiaoran; Beck, Todd; Dhana, Klodian; Agarwal, Puja; Tangney, Christy; Evans, Denis; Rajan, Kumar
Abstract: Objectives: We aim to 1) examine the association of whole grain consumption and rate of decline in global cognition, perceptual speed, episodic memory and 2) test whether these associations differ by race/ethnicity. Methods: We included 4, 719 participants from a biracial population-based sample, the Chicago Health and Aging Project (62% African Americans [AAs], 63% female) who responded to a FFQ and with two or more cognitive assessments and a follow-up up to 10 years. We excluded those with extreme BMI (<14 or >55) and implausible caloric intakes (<500 kcal or > 3800 kcal for women, < 800 kcal or > 4200 kcal for men), or entire page or >50% items unanswered. Global cognition was assessed using a composite score of episodic memory, perceptual speed, and the MMSE. Diet was assessed by FFQ. Mixed models were adjusted for age, sex, education, smoking status, calorie intake, cognitive activities, cardiovascular diseases, time since baseline, and the interaction term of time with each covariate. Results: On average, AAs had higher whole grain consumption (1.3 ± 1.03 servings/d) than European Americans (EAs, 0.9 ± 0.8 servings/d, P < 0.05). Higher consumption of whole grains was associated with a slower global cognitive decline (P for trend 0.004). Specifically, the association of whole grain consumption and slower rate of decline in global cognition, perceptual speed, and episodic memory was observed in AAs, but not among EAs. Among AAs, those in the highest quintile had a 38% slower rate of decline in global cognition (β = 0.024, P = 0.004), 54% for perceptual speed (β = 0.023, P = 0.006), and 70% for episodic memory (β = 0.028, P = 0.015) compared to those in the lowest quintile. In terms of the amount consumed, in AAs, participants who consumed >3 servings/d versus those who consumed < 1 serving/d, had a slower rate of decline in global cognition (38% slower, P = 0.0093), perceptual speed (79% slower, P = 0.014) and episodic memory (65% slower, P = 0.014). In EAs with >3 servings/d, we did not find a significant association in global cognitive decline (38% slower, P = 0.08) than those who consumed < 1 serving/d. Conclusions: Whole grain consumption is suboptimal in the study population. Improving the consumption of whole grains can lower rate of decline in global cognition, perceptual speed, and episodic memory, especially among AAs. Funding Sources: R01AG03154, R01AG051635, RF1AG057532, R01AG058679.